A novel protocol to characterize the thermal protective performance of fabrics in hot-water exposure. (July 2016) - Mandal, Sumit; Song, Guowen; Gholamreza, Farzan
This study aims to introduce a novel protocol to characterize the thermal protective performance of fabrics used in firefighters' clothing under hot-water exposure. For this, new and improved test methods were developed to evaluate the performance of a set of fabrics under exposure to hot-water splash and hot-water immersion with compression. The thermal energy transmission through the fabrics tested was thoroughly investigated, and the physical properties that affect the performance of fabrics were statistically identified. It has been found that mainly mass (hot-water) transfer occurs through fabrics in a hot-water splash; whereas, both conductive heat and mass transfer predominate in a hot-water immersion with compression. The compression applied in the exposure of hot-water immersion changes the physical properties of fabrics, thereby reducing fabrics' performance. The structural configuration and physical properties (e.g., air permeability, thickness) of fabrics are crucial to their heat and mass transfer and therefore to overall fabric performance. This study's findings may contribute to developing new fabric testing standards, as well as improved thermal protective clothing to provide better occupational safety and health for firefighters.